Primary signet ring cell histology does not portend worse survival for early stage lung cancer following lobectomy. (February 2022) - Peng, Terrance; Yau, Anita; Ding, Li; David, Elizabeth A.; Wightman, Sean C.; Atay, Scott M.; Kim, Anthony W.
Introduction: Signet ring cell (SRC) histology is considered a poor prognostic factor in various cancers. However, primary SRC lung adenocarcinoma is rare and poorly understood. Methods: The National Cancer Database was queried to identify treatment-naïve patients who received lobectomy for primary SRC or non-SRC pT1-2N0 lung adenocarcinoma <4 cm within four months of diagnosis. SRC lung adenocarcinoma was defined by ICD-O-3 code 8490, while non-SRC lung adenocarcinoma was defined by ICD-O-3 codes 8140, 8141, 8143, 8147, 8255, 8260, 8310, 8481, 8560, and 8570–8574. The Kaplan-Meier curve and log-rank test was used to compare five-year OS between SRC versus non-SRC lung adenocarcinoma cohorts. The impact of SRC histology on risk of death was assessed using the Cox proportional hazards regression model. Results: 48, 399 patients were included in this study: 62 with primary SRC lung adenocarcinoma and 48, 337 with non-SRC lung adenocarcinoma. The mean age of the overall cohort was 67.0 ± 9.6 years. Five-year OS following lobectomy did not differ significantly between SRC lung adenocarcinoma and non-SRC lung adenocarcinoma cohorts (SRC 73.9% vs. non-SRC 69.3%, p  = 0.64). SRC histology did not significantly impact risk of death within five years after lobectomy (HR 0.89, p  = 0.66). Conclusions: Following lobectomy for pT1-2N0 tumors <4 cm, patients with primary SRC lung adenocarcinoma do not experience worse five-year OS or increased risk of death within five years relative to those with non-SRC lung adenocarcinoma. Additional study, including exploration of emerging molecular profiling data, may serve to better define optimal treatment for this histopathologic group of lung adenocarcinomas.